Legal Protection Against Trademark Counterfeiting in Micro, Small, and Medium Enterprise Products in Banyumas Region - Dwi Febriyanti; Maya Ruhtiani; Alan Bayu Aji (Jurnal Hukum In Concreto, 2025)
This study investigates trademark counterfeiting in micro, small, and medium enterprises (MSMEs) in the Banyumas region. It aims to understand and analyze the legal framework for protection against trademark counterfeiting under Law No. 20 of 2016 on Trademarks and Geographical Indications and to evaluate the legal protection for MSME products in Banyumas. The research employs a juridical-empirical method using both legislative and case-based approaches. Data types and sources include primary and secondary data collected through observation, interviews, and documentation, with qualitative data analysis techniques. The results indicate that legal provisions allow for criminal sanctions for trademark counterfeiting, as Articles 100 and 102 specified. In addition to criminal penalties, counterfeiters may also face civil sanctions, including compensation claims or cessation of all activities related to using the counterfeit trademark, as outlined in Article 83. However, legal protection against trademark counterfeiting for MSME products in Banyumas is still not optimal.